Prototipe Aplikasi Lacak Posisi Berbasis Java 2 Micro-Edition - Teguh Susyanto (Jurnal Ilmiah SINUS, 2011)
Location-Based Service (LBS) is a technology based on device location information service called the Global Positioning System (GPS). Along with many types of mobile phones or handheld devices with GPS support has been widely available in the market with a relatively affordable price, this is quite advantageous, especially to be developed into effective technology-based location using a GPS device. This technology has been widely implemented to support specific business areas such as detection tools for security systems, the route guide in the transportation and tourism, and also for other fields that use geographic location systems. In this paper the author build a prototype application Tracking Position using GPS on a mobile device. That can later be exploited for the benefit in the field of transportation and security. This application is developed using Java 2 Micro Edition platform and JSR-179 Location API, as a simulation of detection of the existence of tools that can be monitored via computer by using the Internet Networks.Keyword : Location-Based System, GPS, Lacak Posisi, J2ME